Peculiarities of Action of Catecholamines and their Metabolites in the Regulation of Cardiomyocyte Enzymes - Tapbergenov, Salavat; Sovetov, Bakytbek; Kairkhanova, Ynkar; Smailova, Zhanargul (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Myocardial ischemia is accompanied by a significant increase in adrenaline content in the heart. By its nature, sympathetic hyperactivation is accompanied by increased formation of products of enzymatic and nonenzymatic metabolism of adrenaline and its analogs, which can change the use of ATP by cells, change the activity of mitochondrial and cytosolic enzymes, contributing to disruption of bioenergetic adaptation, antioxidant defense system and levels of intercellular modulators such as AMP and adenosine. AIM: The study objective was to explore the features of adrenaline and its analogs in the regulation of the activity of mitochondrial and cytoplasmic enzymes of cardiomyocytes. METHODS: The experiment was carried out on 65 3-month-old male Wistar rats weighing 60–190 g. To study the effects of catecholamines and their metabolites in the regulation of mitochondrial and cytoplasmic enzymes activity of cardiomyocytes, experimental rats were put to death by intraperitoneal injection of 10% ketamine in an amount of 0.25 mg/100 g. Activity of mitochondrial succinate dehydrogenase, cytochrome c oxidase, mitochondrial DNP-activated ATPase, adenosine deaminase (AD), AMP deaminase (AMPD), glutathione reductase, and glutathione peroxidase were determined. RESULTS: Dopamine has the greatest activating effect on cardiac mitochondrial ADH, adrenaline on CHO, and adrenochrome and adrenoxyl on ATPase. Isadrine and dopamine reduce cardiac AMPase activity. An activating effect on cardiac mitochondrial AMPD was found only in norepinephrine. CONCLUSION: In cardiomyocytes, adrenaline, activates cytosolic enzymes of purine nucleotide metabolism AD and AMPD, as well as increases the level of lipid peroxidation (MDA and DC). This proves that adrenaline acting on adrenoreceptor mechanisms leads the body into a state of oxidative stress. Hormone-mediators of the sympatho-adrenal system adrenaline, dopamine, noradrenaline, isadrine, and catecholamine metabolites (adrenochrome and adrenoxyl), changes the activity of mitochondrial respiratory chain enzymes of cardiomyocytes, also regulate tissue respiration processes, putting mitochondria into the state of “loose” coupling of respiration and phosphorylation.